A flocking-inspired algorithm for fair resource allocation in vehicle-mounted mobile relays. (1st May 2017) - Choi, Hyun-Ho; Lee, Jung-Ryun
Abstract: In this paper, we apply the bio-inspired flocking algorithm to fair resource allocation in vehicle-mounted mobile relay (VMR) deployed networks. Although a VMR-deployed network has an advantage of the provision of high-quality communication services to mobile devices inside the vehicle, it is more susceptible to inter-VMR and base station (BS)-VMR interferences because both the mobility and geographical position of the VMRs and pedestrian mobile stations (MSs) cannot be artificially controlled. Therefore, the proposed flocking-inspired algorithm is designed to achieve the adaptive alleviation of the inter-VMR and BS-VMR interferences, and the attainment of a fair and distributed resource allocation among competing VMRs. We analyze the convergence of the proposed flocking-inspired algorithm and verify its self-adaptiveness under the dynamically changing network topology. Further, we construct a cellular simulation environment in consideration of two-way four-lane and three-way intersection road scenarios and then evaluate the throughput performance of the proposed method in the context of the IEEE 802.16j relay network. The results show that the proposed flocking-inspired resource allocation method adaptively alleviates the inter-VMR and BS-VMR interferences, and enhances the throughput performance beyond that of a conventional method.